The different damage patterns of short-, middle- and long-range connections between patients with relapse-remitting multiple sclerosis and neuromyelitis optica spectrum disorder - Chen, Xiaoya; Peng, Yuling; Zheng, Qiao; Luo, Dan; Han, Yongliang; Luo, Qi; Zhu, Qiyuan; Luo, Tianyou; Li, Yongmei (Frontiers in Immunology, 2022)
Objective To investigate the differences in short-, middle- and long-range connections between patients with relapse-remitting multiple sclerosis (RRMS) and neuromyelitis optica spectrum disorder (NMOSD), and their correlation with brain tissue volume, structural and functional network parameters. Methods A total of 51 RRMS, 42 NMOSD and 56 health controls (HC) were recruited. Of these 25 RRMS (median: 1.37 years) and 20 NMOSD (median: 1.25 years) patients were also studied at follow-up. The whole-brain fiber connection was divided into three groups according to the trisected lengths of the tract in HC group, including short-, middle- and long-range connections. The brain tissue features (including total brain tissue and deep grey matter volumes) and parameters of DTI and functional networks (including the shortest path, clustering coefficient, local efficiency and global efficiency) were calculated. The differences in fiber number (FN) and average fractional anisotropy (FA) were compared between RRMS and NMOSD by the One-way ANOVA and post hoc tests. The correlation between the FN or FA and the brain tissue volume, DTI and functional network parameters were further analyzed by Pearson analysis. Results Compared to HC and NMOSD, the total number of fibers in RRMS was decreased, including the reduced FN of middle- and long-range connections, but increased FN of short-range connections. Compared to HC, the FA of three fibers in RRMS and NMOSD were reduced significantly, and the decrease of FA in RRMS was greater than in NMOSD. There were correlations between the FN of short-, and long-range connections and the atrophy of whole brain tissue in two diseases and structural network topological parameters in RRMS. Additionally, there was no significant difference of FN and FA in short-, middle- and long-range connections between the baseline and follow-up in two diseases. Conclusions RRMS and NMOSD patients have different patterns of fiber connection damage. The FN of different lengths in RRMS and NMOSD patients may be associated with brain atrophy. The FN and FA of different lengths may explain the decreased efficiency of the structural network in RRMS patients. In the short-term follow-up, neither has worsened damage of different fibers in two diseases.